Micelas de copolímeros em bloco à base de maltoheptaose contendo ftalocianina de magnésio para aplicação em terapia fotodinâmica - Mattiazzi, Lia Mallmann (2022)
The development of new nanocarriers for the so-called third-generation photosensitizers (FS) has contributed significantly to the evolution of photodynamic therapy (PDT). Due to its maximum absorption at wavelengths within the phototherapeutic window range (600-800 nm), low photochemical degradation, and adequate singlet oxygen quantum yield (ФΔ), magnesium phthalocyanine (MgPc) is considered a promising FS for use in PDT. However, its high hydrophobicity and formation of aggregates decrease its photodynamic activity in a physiological environment. Thus, the encapsulation of MgPc in nanostructures becomes necessary to improve its bioavailability and increase its phototherapeutic activity. From these considerations, the main objective of this work is to encapsulate MgPc in polymeric micelles obtained from block copolymers based on maltoheptaose (MH) and evaluate its photodynamic activity. By way of comparison, the encapsulation of MgPc in poly-ɛ-caprolactone (PCL) nanocapsules was also performed. The physicochemical characterization of the nanostructured systems (MH-b-PS@MgPc, MH-b-PMMA@MgPc, and PCL@MgPc) was carried out by determining the values of hydrodynamic diameter, polydipersion index, zeta potential, the total content of MgPc, encapsulation efficiency and physical stability over time by LUMiSizer. The photodynamic activity of the nanoparticles was evaluated by monitoring the photochemical degradation reaction of the chemical suppressor 1,3-diphenylisobenzofuran (DPBF). The kinetic profile of in vitro release of MgPc from the nanostructures and the toxicity and biodistribution of the nanocarriers against the nematodes Caenorhabditis elegans were also evaluated. The nanostructures presented nanometric sizes, low polydispersion indices (which confirm the homogeneity of the systems), negative zeta potential with high modulus values, and encapsulation efficiency above 95%. Analysis by LUMiSizer revealed that the polymeric micelles are highly stable in aqueous medium, with an estimated physical stability of three years. Evaluating the photodynamic activity of the nanoparticles it was concluded that polymeric micelles containing FS are capable of generating singlet oxygen at satisfactory levels for use in PDT, with Ф values close to those of unencapsulated MgPc. The nanostructures present a sustained FS release profile, with biexponential model kinetics. The toxicity study showed that the nanoparticles cause a small reduction in the larval development of C. elegans, but do not induce lethality when the worms are exposed to low concentrations, and that they are mostly located in intestinal cells. Considering these results, it is concluded that nanostructured systems based on maltoheptaose are promising carriers for MgPc, with potential use in PDT.